A Rare Case of Cutaneous Ulcer Caused by Pseudomonas Putida - Dina Arwina Dalimunthe; Michael Andrianus (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cutaneous ulcers are commonly caused by bacterial infections, most frequently Staphylococcus aureus. However, infection caused by Pseudomonas putida is extremely rare in humans. Pseudomonas putida is a gram-negative, obligate aerobic bacterium widely found in soil, water, and moist environments and is generally considered non-pathogenic. Nevertheless, under certain conditions, it may act as an opportunistic pathogen and cause infection, particularly in the presence of open wounds or environmental exposure. This report describes a rare case of a cutaneous ulcer caused by Pseudomonas putida in a 26-year-old male laborer. The patient presented with multiple painful ulcers with erythematous edges and purulent discharge on the anterior and lateral regions of the left foot. The lesions initially developed after minor trauma caused by a plant prick while working in a rice field. Laboratory investigations including pus culture revealed growth of Pseudomonas putida without fungal infection. Antibiotic susceptibility testing showed sensitivity to amikacin, gentamicin, and meropenem. The patient was treated with oral ciprofloxacin, topical gentamicin, analgesics, and saline compresses, resulting in gradual clinical improvement with resolution of the ulcers and residual hyperpigmented macules.